Antibacterial Effects of Grapes Seed Extract on Methicillin Resistant Staphylococcus Aureus and Extended Spectrum Beta Lactamase Producing Escherichia Coli and its Comparison with Linezolid and Meropenem (Medical Forum Monthly, 2021)
Objective: Antibacterial effects of grapes seed extract on methicillin resistant staphylococcus aureus and extended spectrum beta lactamase producing escherichia coli and its comparison with linezolid and meropenem.Study Design: It is a Pre-Clinical (in-vitro) studyPlace and Duration of Study: This study was conducted at the Ziauddin University, Karachi from January 2020 to October 2020 for a period of 10 months.Materials and Methods: Patients age were 10 to 80 years, both genders, showing signs and symptoms of bacterial infections were selected. All clinical samples were collected in the form of pus, urine, blood, tracheal aspirations, patients admitted in surgical and medical wards, intensive care units and outdoor patients, who were attending clinics. All these samples were transported to Clinical Microbiology Laboratory, Ziauddin hospital, North Nazimabad campus and then culture and sensitivity test were performed there. Sample showing double growth and contamination on agar plates were excluded from study.Results: Total 80 samples were collected. 40 samples were Methicillin Resistant Staph Aureus (MRSA) and 40 samples were Extended Spectrum Beta Lactamase Producing Escherichia Coli (ESBL E Coli). Female to male samples ratio of 1.35:1. Methicillin Resistant Staph Aureus commonly found in pus swab 15(37.5%) and 21(52.5%) ESBL Producing E Coli found in urine samples. Anti-bacterial activity of Grapes seed extracts observed against Methicillin Resistant Staph Aureus at different levels of concentration 37(92.5%), 37(92.5%), 37(92.5%), 40(100%) and 40(100%) at different dilutions at 20 mg/ml, 30 mg/ml, 40 mg/ml and 40 (100%) respectively. While less resistance was observed of Methicillin Resistant Staph Aureus at different concentration level of Grapes seed extracts. More resistance was observed of Grapes seed extracts against ESBL E coli at different concentration reported about 97-100%. While sensitivity of ESBL E coli was observed only in 3 sample at different concentration level of Grapes seed extracts about 2.5%. Compare the results of sensitivity of GSE with linezolid and meropenem against ESBL E coli and found significant p value <0.05.Conclusion: The grape seed extract has shown excellent antimicrobial activity against methicillin resistant Staph aureus and resistant strains of ESBL producing E. coli.